Experimental infection of sheep with Bhanja virus - Mádr, V; Hubálek, Z; Zendulková, D (Folia parasitologica, 1984)
Seven juvenile sheep were infected subcutaneously (s.c.) or intracerebrally (i.c.) with Bhanja virus. Distinct symptoms of CNS affection (ataxia, pareses) were observed only in the case of i.c. application of a massive dose (10(-7) to 10(9) SMicLD50) of the Bg 336/336 strain. A short-term and low viremia (one to four days p.i.) was ascertained after i.c. infection with a dose of 10(4.7) to 10(9.2) SMicLD50 of the same strain. On the other hand, the high titres of neutralization antibodies were detected even after inoculation of small doses of the virus (e.g. 50 SMicLD50). Unlike the symptomatic response, the immune response of sheep to Bhanja virus is high.
Keywords: Sheep; Ataxia; Female; zvířata; Viremia; Disease Susceptibility; náchylnost k nemoci; Bunyaviridae; Sheep Diseases; ženské pohlaví; Male; Paresis; paréza; protilátky virové; Bunyaviridae Infections; Antibodies, Viral; Animals; infekce viry z čeledi Bunyaviridae; viremie; mužské pohlaví; ataxie; nemoci ovcí; ovce